PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS KEARIFAN LOKAL KELAS V SDN 118 PALEMBANG - Rohman Fauzi; Neta Dian Lestari; Sylvia Lara Syaflin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Technological development demands innovation in elementary school learning so that the learning process becomes more effective, efficient, and attractive. This study aims to develop educational game learning media based on local wisdom for Grade V students of SD Negeri 118 Palembang that is valid and practical. The study used the Research and Development method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial subjects consisted of 4 students for the one-to-one test and 10 students for the small group test. Data were collected through interviews, observation, expert validation questionnaires, and student response questionnaires. Validation was carried out by media experts, material experts, and language experts, while practicality was measured from students' responses after using the product. The validation results showed that the media was declared "Very Valid" with an average of 89.44%, consisting of from media validators 85%, material experts 93.33%, and language validators 90%. The practicality test results at the one-to-one stage were 91%, small group 87.2%, and large group test 89.29%, thus included in the “Very Practical” category. During the trials, students appeared enthusiastic, active, and spirited. Keywords: Educational game, local wisdom, ADDIE, validity, practicality.